Direct cost analysis of the second year post-allogeneic hematopoietic stem cell transplantation in the Bone Marrow Transplant Centre of Tunisia - Myriam Razgallah Khrouf; Leila Achour; Asma Thabti; Mohamed Ali Soussi; Nour Abdejelil; Olfa Lazreg; Chema Drira; Aida Zahaf; Saloua Ladab; Tarek Ben Othman (Taylor & Francis Group, 2017)
Background: Hematopoietic stem cell transplantation (HSCT) is a medically complicated therapy with a long recovery time. In Tunisia, the National Health Insurance Fund (CNAM) covers only the first year post-transplantation, after which the costs are borne by the hospital. Objective: Describe complications that can occur during the second year post-allogeneic HSCT and calculate direct costs in different groups of patients. Methods: In this pharmacoeconomic study, medical records of the second year post-allogeneic HSCT were collected. Studied variables included frequent observed complications and medical and non-medical direct costs. Results: The average total direct cost in the population during the second year post-transplantation was $11,571, 97% of which represents direct medical costs Drugs accounted for the largest share (80%) of total direct costs, dominated by the cost of antifungals (52%) and antivirals (26%) drug . Cytomegalovirus status was seen in 9.3% of patients and was associated with a seven-fold increase in direct costs (p < 0.001).​​In patients who developed chronic GVHD, the average direct cost was three times higher than for those who did not (p = 0.032). Conclusion: Given the importance of direct costs in the post-transplantation period a review of the hospital financing mechanism and a new convention with the CNAM is crucial.​​